THE USE OF COLLABORATIVE STRATEGIC READING (CSR) TO IMPROVE STUDENTS’ READING COMPREHENSION IN THE SECOND GRADE STUDENTS OF SMP NEGERI 2 TARAKAN - Sawitri, Era; Rianto, Agus (Borneo Journal of English Language Education, 2019)
The purpose of this study was to look for the effectiveness of using collaborative strategic reading technique to improve reading comprehension of second grade students at SMP Negeri 2 Tarakan. This   research    was   Quasi-Experimental    design.    Purposive    sampling technique  was used to collect the sample.  There were  two classes  obtained  as samples in this research, they were experimental class and control class. Experimental class (VIII C) was treated by using collaborative strategic reading technique. Control class (VIII A) was treated by using cooperative learning technique.  Each  class  consisted  of  32  students  of  SMP  Negeri  2  Tarakan  in academic year 2018/2019. The instrument of this research was reading tests that consisted of pre-test and post-test. In analyzing the data, the researcher used an independent sample t-test in the SPSS v.24.0. The  results  show  that there  were  significance  difference  in the students’ score of experimental class and the control class. This is indicated by the students’ mean score of pretest and posttest. The mean score of the experimental class in pretest was 40.50 and in posttest was 71.75. It was indicated that the mean score in the experimental class has increased to 31.25. The mean score of the control class in pretest was 44.38 and in posttest was 64.13. It was indicated that the mean score in the control class has increased to 19.75. It is proven that the results of the experimental   class   were   higher   than   the   control   class.   Results   from   the independent sample T-test and T-table from pretest was 1.117 and posttest was 2.335 and the T-table was 1.998 or in pretest was 1.117 1.998 and in posttest was 2.335 1.998. In other words, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. The results of data analysis proved that the results  of teaching  reading  comprehension  by using  collaborative  strategic reading technique was higher than by using cooperative learning technique. Based on  the  explanation  above,  it  can  be  concluded  that  the  collaborative  strategic reading   technique   was  more   effective   than  by  using   cooperative   learning technique.